Pimarane diterpenes from Kaempferia pulchra - Patoomratana Tuchinda (2018)
Two novel pimarane diterpenes, 2α-acetoxysandaracopimaradien-1α-ol and sandaracopimaradien-1α,2α-diol, have been isolated from the hexane extract of the rhizomes of Kaempferia pulchra. Ethyl 4-methoxy-trans-cinnamate is also reported from the same source. The structures were assigned by spectroscopic methods. A single-crystal X-ray diffraction analysis confirmed the structure of 2α-acetoxysandaracopimaradien-1α-ol. © 1994.